A whole animal chemical screen approach to identify modifiers of intestinal neutrophilic inflammation. (9th January 2017) - Oehlers, Stefan H.; Flores, Maria Vega; Hall, Christopher J.; Wang, Liuyang; Ko, Dennis C.; Crosier, Kathryn E.; Crosier, Philip S.
Abstract : By performing two high‐content small molecule screens on dextran sodium sulfate‐ and trinitrobenzene sulfonic acid‐induced zebrafish enterocolitis models of inflammatory bowel disease, we have identified novel anti‐inflammatory drugs from the John Hopkins Clinical Compound Library that suppress neutrophilic inflammation. Live imaging of neutrophil distribution was used to assess the level of acute inflammation and concurrently screen for off‐target drug effects. Supporting the validity of our screening strategy, most of the anti‐inflammatory drug hits were known antibiotics or anti‐inflammatory agents. Novel hits included cholecystokinin (CCK) and dopamine receptor agonists. Using a pharmacological approach, we show that while CCK and dopamine receptor agonists alleviate enterocolitis‐associated inflammation, receptor antagonists exacerbate inflammation in zebrafish. This work highlights the utility of small molecule screening in zebrafish enterocolitis models as a tool to identify novel bioactive molecules capable of modulating acute inflammation. Abstract : Inflammatory bowel disease (IBD) is a chronic condition in which neutrophils infiltrate the intestine, triggering inflammation that leads to loss of intestinal function. To identify new therapeutic avenues for intervention, Oehlers and colleagues used two zebrafish models of enterocolitis to screen the John Hopkins Clinical Compound Library for small molecules that limit neutrophilic inflammation. After validation, 23 compounds with a wide range of indications were reported to decrease neutrophil mobilization. The authors went on to show that the dopamine receptor agonist cabergoline and the cholecystokinin receptor agonist sincalide reduced neutrophilic inflammation in vivo, suggesting their potential therapeutic use in IBD.